Long-Term Heavy Ketamine Use is Associated with Spatial Memory Impairment and Altered Hippocampal Activation - Morgan, Celia J. A.; Dodds, Chris M.; Furby, Hannah; Pepper, Fiona; Fam, Johnson; Freeman, Tom P.; Hughes, Emer; Doeller, Christian; King, John; Howes, Oliver; Stone, James M. (Frontiers in Psychiatry, 2014)
Ketamine, a non-competitive N-methyl-D-aspartate receptor antagonist, is rising in popularity as a drug of abuse. Preliminary evidence suggests that chronic, heavy ketamine use may have profound effects on spatial memory but the mechanism of these deficits is as yet unclear. This study aimed to examine the neural mechanism by which heavy ketamine use impairs spatial memory processing. In a sample of 11 frequent ketamine users and 15 polydrug controls, matched for IQ, age and years in education. We used fMRI utilising an ROI approach to examine the neural activity of three regions known to support successful navigation; the hippocampus, parahippocampal gyrus and the caudate nucleus during a virtual reality task of spatial memory. Frequent ketamine users displayed spatial memory deficits, accompanied by and related to, reduced activation in both the right hippocampus and left parahippocampal gyrus during navigation from memory, and in the left caudate during memory updating, compared to controls. Ketamine users also exhibited schizotypal and dissociative symptoms that were related to hippocampal activation. Impairments in spatial memory observed in ketamine users are related to changes in medial temporal lobe activation. Disrupted medial temporal lobe function may be a consequence of chronic ketamine abuse and may relate to schizophrenia-like symptomatology observed in ketamine users.